Feasibility of administering the WAIS-IV using a home-based telehealth videoconferencing model. Issue 3 (14th March 2022) - Mahon, Susan; Webb, James; Snell, Deborah; Theadom, Alice
Abstract: Objective: : Use of telehealth to deliver neuropsychological services has proven to be a feasible approach, however, there is limited research which has examined the reliability of home-based assessment models using a comprehensive intelligence test. The aim of this study was to examine the reliability and feasibility of a home-based videoconferencing administration of the Wechsler Adult Intelligence Scales-4 th Edition (WAIS-IV). Method: : Thirty healthy participants (aged 18–40 years) completed the WAIS-IV both in-person and via home-based videoconferencing utilizing a randomized counter-balanced methodology to attempt to control for an order effect. Paper record forms for Coding/Symbol Search and Blocks were sent and returned via tamper proof courier packs. Participants completed an online survey of their experiences of TNP following completion of their assessments. Group mean comparisons, intra class correlation coefficients (ICCs) and Bland-Altman measures of bias were calculated. Results: : Findings from both modalities were highly concordant across all WAIS-IV subtests and indices, with all ICCs rated as "excellent, " (≥0.9). There were no significant mean group differences and no evidence of proportional bias. The majority of participants were very satisfied with the use of videoconferencing as an application for cognitive assessment and high levels of participant compliance were observed. Conclusions: : In this non-clinical cohort home-based videoconference administration of the WAIS-IV was feasible, reliable and acceptable. TNP may offer an alternative for those consumers where there are challenges in accessing a face-to-face service delivery model, thereby improving equity, and enabling continuation of service delivery. Future research is needed with a larger and more ethnically diverse clinical population.